Materia Magica : The Archaeology of Magic in Roman Egypt, Cyprus, and Spain - Wilburn, Andrew, 1974- (Book collections on Project MUSE., 2012)
Through three case studies, this book identifies specific forms of magic that may be otherwise unknown. It isolates the practitioners of magic and examines whether magic could be used as a form of countercultural resistance. The author discovers magic in the objects of ancient daily life, suggesting that individuals frequently turned to magic, particularly in crises. Local forms of magic may have differed, and the author proposes that the only way we can find small-town sorcerers is through careful examination of the archaeological evidence. The author develops a method for identifying and interpreting the material remains of magical practice by assessing artifacts within their archaeological contexts.